Answer:
sorry but i cant see the anwser choices
Step-by-step explanation:
Answer:
first we need to substitute g(t) value in h(t) value and then evaluate the expression as follows :
h(g(t))=3(t-1)²+4(t-1).
by solving
h(g(t))=3(t²+1-2t)+4t-4
h(g(t))=3t²-2t-1 will.be the final answer
Answer:
x=2
Step-by-step explanation:
You would first subsitute the y with 13. The you would subtract 3 from 3 and 13. Then you would have 10=5x. Then you would divide 5 by 5 and 10. You will get x = 2
:)
Answer:
da one in the middle and i do relize this is a test becuse i just took it.
Step-by-step explanation:
Question
x+5/x+2 - x+1/x²+2x
Answer:
= (x² - 4x - 1)/[x (x+2)]
= (x² - 4x - 1)/[x² + 2x]
Step-by-step explanation:
x + 5/x + 2 - x + 1/x² + 2x
We factorise the second denominator to give us :
x + 5/x + 2 - x + 1/x(x + 2)
We find the L.C.M of both denominators which is x(x+2).
[x(x + 5)-(x + 1)] / (x (x + 2))
Expand the bracket
=[x² +5x - x -1] / [x (x + 2)]
=(x² - 4x - 1) / [x (x + 2)]
= (x² - 4x - 1)/ [x (x + 2)]
= (x² - 4x - 1) / [x² + 2x]